1998
DOI: 10.1111/j.1744-7348.1998.tb05215.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light leaf spot (Pyrenopeziza brassicae) on yield of winter oilseed rape (Brassica napus)

Abstract: The relationship between development of light leaf spot and yield loss in winter oilseed rape was analysed, initially using data from three experiments at sites near Aberdeen in Scotland in the seasons 1991/92, 1992/93 and 1993/94, respectively. Over the three seasons, single-point models relating yield to Light leaf spot incidence (% plants with leaves with light leaf spot) at GS 3.3 (flower buds visible) generally accounted for more of the variance than single-point models at earlier or later growth stages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 6 publications
(6 reference statements)
0
17
0
Order By: Relevance
“…Accurate predictions of the risk of severe epidemics are therefore needed to guide decisions about fungicide applications. Su et al . (1998) demonstrated a relationship between incidence (percentage of plants affected) of light leaf spot at growth stage (GS) 3·3 (Sylvester‐Bradley & Makepeace, 1985) in spring and percentage yield loss at harvest, with approximately 10% yield loss for each additional 30% plants affected by light leaf spot.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate predictions of the risk of severe epidemics are therefore needed to guide decisions about fungicide applications. Su et al . (1998) demonstrated a relationship between incidence (percentage of plants affected) of light leaf spot at growth stage (GS) 3·3 (Sylvester‐Bradley & Makepeace, 1985) in spring and percentage yield loss at harvest, with approximately 10% yield loss for each additional 30% plants affected by light leaf spot.…”
Section: Introductionmentioning
confidence: 99%
“…Light leaf spot, caused by the pathogen Pyrenopeziza brassicae , is one of the two most important diseases of winter oilseed rape in the UK (Su et al ., 1998). Yield losses of up to £40 million per annum have been estimated in recent years (Gladders, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Regression analyses of position and parallelism had shown that the data for the two growing seasons were fitted best by a single line rather than two lines, and other tests had shown that they were fitted better by a linear relationship than a curve (polynomial equation logit(p) = log(p/1-p)(data were logit-transformed to normalise the variance), T s was mean temperature in the previous summer (July/August) before the crop was sown and R w mean monthly rainfall during winter (December to February) when the crop was at the rosette growth stage. The predictions of light leaf spot incidence for each site and scenario were then used to calculate predicted yield loss for each site and scenario using a modified version of the yield loss model derived by Su et al (1998).…”
Section: Phoma Stem Canker/light Leaf Spot Yield Loss Predictionsmentioning
confidence: 99%